PENGUATAN LITERASI DIGITAL MAHASISWA MELALUI PELATIHAN PEMBUATAN WEBSITE OTOMATIS BERBASIS ARTIFICIAL INTELLIGENCE - Yunus Anis; Retnowati; Sri Mulyani; Sunardi; Purwatiningtyas (CV. Nature Creative Innovation, 2026)
This community service activity was motivated by the school's need to improve digital literacy, particularly the ability to create web-based information media independently, creatively, and responsibly. Many students are already familiar with using the internet and social media, but not all of them have the productive skills to design, compose content, and publish websites. The development of artificial intelligence (AI) opens new opportunities for students to assist schools in creating school visual designs. The objectives of this activity are to improve students' understanding of digital literacy, introduce ethical use of AI, and train students to create simple automated websites for school profiles, classes, portfolios, and school activity information. The implementation method includes needs assessment, pretest, material delivery, demonstration, guided practice, project mentoring, posttest, and product evaluation. The activity was designed for TRMG students using a project-based workshop approach. The evaluation results showed an increase in students' abilities in aspects of AI understanding, prompt development, website structure, interface design, website publication, and digital ethics. The outputs of the activity were a school website prototype, training modules, and improvements in AI-based digital literacy. This program demonstrates that AI-based automated website training can be a practical strategy for strengthening digital competency in schools.